Filling the Gondwanan gap: paleobiogeographic implications of new crinoids from the Castillejo and Fombuena formations (Middle and Upper Ordovician, Iberian Chains, Spain). (8th February 2017) - Cole, Selina R.; Ausich, William I.; Colmenar, Jorge; Zamora, Samuel
Abstract: A diverse crinoid fauna is described from the Upper Ordovician (Katian) Fombuena Formation from the eastern Iberian Chains of Spain. New crinoids include the diplobathrid camerates Fombuenacrinus nodulus n. gen. n. sp., Goyacrinus gutierrezi n. gen. n. sp., Dalicrinus hammanni n. gen. n. sp., and Ambonacrinus decorus n. gen. n. sp.; the monobathrid camerate Eopatelliocrinus hispaniensis n. sp.; and the cladid Picassocrinus villasi n. gen. n. sp. A new occurrence of Heviacrinus melendezi Gil Cid, Domínguez Alonso, and Silván Pobes, 1996 is also documented from the Castillejo Formation (Darriwilian, Middle Ordovician) from the eastern Iberian Chains of Spain. The Fombuena Formation comprises a Gondwanan crinoid assemblage from a high paleolatitude and has the highest crinoid diversity of any currently known Katian Gondwanan fauna. This assemblage is compared to other Katian age faunas around the globe, and its paleobiogeographic implications are discussed.